Scripting Hitchcock : Psycho, The birds, and Marnie - Raubicheck, Walter, 1950- (University of Illinois Press, 2011)
Drawing from extensive interviews with the screenwriters and other film technicians who worked for Hitchcock, the authors illustrate how much of the filmmaking process took place not on the set or in front of the camera, but in the adaptation of the sources, the mutual creation of plot and characters by the director and the writers.